2004
DOI: 10.1159/000080073
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Fluid Glycoproteins Expressing Sialyl Lewis Carbohydrate Antigens Stimulate Progesterone Production in Human Trophoblasts in vitro

Abstract: Background: Progesterone is thought to mediate immune modulator effects by regulating uterine responsiveness. The aim of the study was to clarify the effect of transferrin and glycodelin A (former name PP14) as sialyl Lewis X-expressing glycoproteins on the release of progesterone by trophoblast cells in vitro. Methods: Cytotrophoblast cells were prepared from human term placentas by standard dispersion of villous tissue followed by a Percoll gradient centrifugation step. Trophoblasts were incubated with varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Because of the limitation of the nutrient supply from amniotic fluid, amniotic epithelial cells face starvation and adapt to this adverse circumstance by inducing autophagy. In amniotic fluid, many hormones appear, such as the growth hormone, insulin (Osmanagaoglu et al, 2005), testosterone, androstenedione (van de Beek et al, 2004), progesterone (Jeschke et al, 2004), thyroid-stimulating hormone (Singh et al, 2003), and human chorionic gonadotropin (Jeschke et al, 2003). Some of these hormones increase during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the limitation of the nutrient supply from amniotic fluid, amniotic epithelial cells face starvation and adapt to this adverse circumstance by inducing autophagy. In amniotic fluid, many hormones appear, such as the growth hormone, insulin (Osmanagaoglu et al, 2005), testosterone, androstenedione (van de Beek et al, 2004), progesterone (Jeschke et al, 2004), thyroid-stimulating hormone (Singh et al, 2003), and human chorionic gonadotropin (Jeschke et al, 2003). Some of these hormones increase during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of LNFPIII/Lewis X has been associated with immunosuppressive states, being found in breast milk, the urine of pregnant women, on the trophoblast, on various tumours and during numerous parasitic and viral infections. [22][23][24][25][26][27][28][29] Previously, we demonstrated that LNFPIII injection induced the expansion of peritoneal macrophages capable of suppressing naïve T-cell proliferation in vitro. 30 Further, administration of LNFPIII was shown to prevent development of psoriatic-like lesions in fsn/fsn mice in vivo.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…These cells express the estrogen receptor alpha and beta [18][19][20] and in addition produce a variety of specific steroid hormones like progesterone and estrogen [21][22][23][24]. Therefore, we measured the effect of phytoestrogens on progesterone and estrogen production of these cells.…”
Section: Introductionmentioning
confidence: 99%